(untitled) (Experimental biology, 2015)
The first two weeks was found to increase of leukocytes neutrophils and the emergence of promonotsity in the blood experimental lymphedema of the lower limb of rat .Observed aggregation of erythrocytes There is a moderate decrease in the percentage of lymphocytes in the lymph and are prone to thrombosis.